Implementation of Maslahah in the LPDB-KUMKM Revolving Fund Loan or Financing Program - Fahamsyah, Mohammad Hatta; Kusumaningtyas, Menur; Fatih, Sultan (Universitas Trunojoyo Madura, 2023)
This research aims to explore the implementation of maslahah in the loan or revolving fund financing program managed by the Cooperative, Micro, Small, and Medium Enterprises Revolving Fund Management Institution (LPDB-KUMKM).The research method used is a literature study with a descriptive qualitative approach. Secondary data was obtained from a variety of sources, including journals, related research, and books relevant to the context of the discussion.The results of the study show that LPDB-KUMKM as a whole has applied the concept of maslahah in its program. This finding is reflected in several aspects. First, LPDB-KUMKM has succeeded in creating economic independence for cooperatives and partner MSMEs through the provision of funds, training, and mentoring. Second, this institution ensures that all programs implemented meet the characteristics of sharia compliance by avoiding elements of riba, gharar, and maisir. Third, this institution also conducts a comprehensive risk evaluation including credit risk, operational risk, and compliance risk. Fourth, LPDB-KUMKM actively empowers the community through training programs, mentoring, and providing access to other resources. Fifth, LPDB-KUMKM applies the principles of accountability and transparency in every stage of its management. Sixth, this institution is actively involved in the process of continuous evaluation and improvement to ensure the efficiency and effectiveness of all programs implemented. The results of this research can be implemented into the economic life of the community by utilizing Maslahah in loan program activities and revolving funds.